PRINCIPLES OF DEVELOPING FOREIGN LANGUAGE LEXICAL COMPETENCE OF UNIVERSITY STUDENTS IN DISTANCE EDUCATION - Monastyrova , L. (Problems of Engineer-Pedagogical Education, 2024)
The article examines the development of students' vocabulary in distance English classes, essential for engaging with professionally relevant texts and discussing topics pertinent to their future careers. This study examines the different stages in which individuals acquire lexical competence, as well as proposes effective strategies for students to enhance their foreign language vocabulary learning. The effective utilization of original literature related to their future field of study greatly benefits students. Developing lexical skills plays a vital role in this process. Specifically, building a semantic and structural typology of scientific and technical terminological vocabulary, as well as identifying and overcoming difficulties in comprehending English, are crucial aspects. Of particular interest is incorporating a thesaurus-focused approach when teaching specialized foreign language vocabulary. This approach takes into consideration the interconnection between the development of a student's thesaurus and the resources provided by the methodical vocabulary system. The author emphasizes the impact of distance learning on the development of foreign language vocabulary skills in university students. The article explores the benefits of using the Moodle platform to enhance the learning of foreign language materials and improve the overall proficiency of future specialists. It proposes a series of exercises that should be incorporated into distance learning courses to ensure a high level of language comprehension, effective communication skills, and the acquisition of necessary linguistic abilities. These exercises also encourage students to independently explore and creatively apply their language skills. In conclusion, the author stresses that the hands-on experience of instructing students in a remote course highlights the immense benefits of completing sets of tasks on the Moodle platform. These tasks, which lay the foundation for teaching foreign language vocabulary, not only provide students with specific terminology, but also equip them with fundamental concepts directly relevant to their future profession. By engaging in real-life situations where this vocabulary is utilized, students are able to develop exceptional foreign language communication skills at an advanced professional level.